The Value of Hepatic Scintigraphy in the Diagnosis of Biliary Atresia - Chan, Wing Ki; Chung, Patrick Ho Yu; Wong, Kenneth Kak Yuen (Frontiers in Pediatrics, 2022)
Introduction Biliary Atresia (BA) requires prompt diagnosis and surgical intervention to optimize its outcome. The aim of this study was to evaluate the accuracy of EHIDA in distinguishing between BA and other causes of cholestatic jaundice. Methods This was a retrospective study of all patients who underwent EHIDA in a tertiary center from 1997 to 2019. The sensitivity, specificity, Negative Predictive Value (NPV) and Positive Predictive Value (PPV) of EHIDA were evaluated. Factors that can potentially affect its accuracy were also analyzed. Results During the study period, 93 patients aged 10 to 110 days with cholestasis and suspected BA underwent EHIDA. The sensitivity and NPV were 91.2 and 85.3% while specificity and PPV were 80.6 and 88.1%. These results suggested that EHIDA is suboptimal in both diagnosing or excluding BA. Out of 59 patients who showed no tracer activities in the intestines after 24 h, 56 were subjected to surgical exploration and 52 (92.9%) were eventually diagnosed BA. The accuracy of EHIDA scan were different by the maturity of the patient, age at testing and severity of cholestasis. Conclusions EHIDA has a limited accuracy and surgical exploration remains the gold standard to establish the diagnosis of BA. Potential confounding factors that may affect the accuracy of EHIDA were identified but require further studies with larger sample sizes to validate.